Black and White: History of Racial Identity in Italy - Giuliani, Gaia (feminists@law, 2014)
Drawing on the book Bianco e nero. Storia dell'identita razziale degli Itallani, this lecture traces the political, cultural and visual history of Italian racial identity from unificaiton to the economic boom, through Fascism and the post-war era. Gaia Giuliani uses analytical categories derived from political philosophy, critical race theory, whiteness studies and postcolonial studies, and examines political theories of race, scientific literature and legislation related to emigration in order to trace the different processes of self-racialisation in the political discourse from the unification period up to 1936. The lecture also looks at contemporary Italian racism, analysing mass culture products (1980s-2007), TV coverage of racist incidents (2010-2012), and the intertwining of masculinity, virility, whtieness and race in Berlusconi's sexual scandals.